10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Ferroptosis is an iron-dependent form of cell death driven by lipid peroxidation. This concept reshapes our understanding of tissue degenerative lesions and oncogenesis. Icariin (ICA) is an isoprenyl flavonol glycoside derived from plants of the genus Epimedium. Acting as a bidirectional regulator of this pathway, it precisely modulates cellular sensitivity to ferroptosis across distinct disease states. This review systematically synthesizes literature from PubMed, ScienceDirect, Web of Science, and Google Scholar (2015-2025). Search keywords included "Icariin", "ferroptosis", "pharmacological mechanism", "pharmacokinetics" and "toxicology", while excluding conference abstracts, non-English studies, and reports lacking raw data. We systematically elucidated the role of ICA across a continuous "mechanism-treatment-metabolism" spectrum: in neurodegenerative disease models, ICA exerts an anti-oxidant effect to maintain cellular homeostasis, whereas in drug-resistant cancer cells, it functions as a pro-oxidant, promoting the elimination of malignant cells. This context-dependent effect is primarily attributed to its modulation of the nuclear factor erythroid 2-related factor 2 (Nrf2)/glutathione peroxidase 4 (GPX4) axis, which serves as the critical "molecular switch" of redox homeostasis. Beyond direct signaling, ICA functions as a natural precursor. Its safety profile and therapeutic window are governed by the metabolic network, potentially conferring advantages over synthetic inhibitors. Although low systemic bioavailability limits clinical translation, nanodelivery systems and synthetic biology strategies offer viable approaches for optimizing its metabolic profile. Ultimately, ICA provides an exquisite molecular blueprint, charting a course for the development of ferroptosis-targeted therapies that can precisely sense and adapt to the microenvironments of complex diseases.